Effects of IMOD™ on angiogenesis, miR-503 and CDC25 expression levels in heart tissue of diabetic male rats - Arshad Ghaffari-Nasab; Fariba Mirzaei Bavil; Rafigheh Ghiasi; Saeed Sadigh-Eteghad; Mohammad Reza Alipour (Mashhad University of Medical Sciences, 2018)
Objective: Diabetes is associated with vascular complications and impaired angiogenesis. Since angiogenesis plays a crucial role in vascular homeostasis in ischemic heart diseases, in this study, the effect of IMOD™ on miR-503 and CDC25 expression level which are altered in impaired angiogenesis were investigated in heart tissue of diabetic rats. Materials and Methods: Forty male Wistar rats (200-250 g) were randomly classified into 4 groups: control (C), IMOD™ (I), diabetes (D), and diabetes+IMOD™ (D+I). For induction of experimental diabetes in animals, a single dose of streptozotocin (STZ; 60mg/kg) was injected intraperitoneally. After 8 weeks of treatment with IMOD™ (20 mg/kg/day), heart tissue samples were removed and used for measurement of miR-503 and CDC25 expression level as well as histological studies. Results: Results of this study showed that diabetes decreased heart tissue angiogenesis which was associated with increased miR-503 and reduced CDC25 expression levels (p